Moyer’s method of mixed dentition analysis: a meta-analysis - Buwembo, William; Luboga, Sam (African Health Sciences, 2004)
Mixed dentition analysis forms an essential part of an orthodontic assessment. Moyer’s method which is commonly used for this analysis is based on data derived from a Caucasian population. The applicability of tables derived from the data Moyer used to other ethnic groups has been doubted. However no meta-analyses have been done to statistically prove this. Objective: To assess the applicability of Moyer’s method in different ethnic groups. Study design: A meta-analysis of studies done on other populations using Moyer’s method. Method: The seven articles included in this study were identified by a literature search of Medline (1966-June 2003) using predetermined key words, inclusion and exclusion criteria. 195 articles were reviewed and meta-analyzed. Results: Overall the correlation coefficients were found to be borderline in variation with a p-value of 0.05. Separation of the articles into Caucasian and Asian groups also gave borderline p-values of 0.05. Conclusion Variation in the correlation coefficients of different populations using Moyer’s method may fall either side. This implies that Moyer’s method of prediction may have population variations. For one to be sure of the accuracy while using Moyer’s method it may be safer to develop prediction tables for specific populations. Thus Moyer’s method cannot universally be applied without question.
Keywords: Meta-analysis; Mixed dentition analysis; Moyer’s method